2019
DOI: 10.3892/ol.2019.10577
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA FLVCR1‑AS1 regulates cell proliferation, migration and invasion by sponging miR‑485‑5p in human cholangiocarcinoma

Abstract: Long non-coding RNA (lncRNA) FLVCR1 antisense RNA 1 (FLVCR1-AS1) serves a crucial role in many types of cancer; however, to the best of our knowledge, the biological effect of FLVCR1-AS1 in cholangiocarcinoma (CCA) remains unclear. The present study aimed to elucidate the involvement of FLVCR1-AS1 in the regulation of human CCA cell growth, migration and invasion, as well as the mechanisms underlying its effect. The expression levels of FLVCR1-AS1 in CCA tumor tissues, adjacent normal tissues, CCA cell lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…It has been reported that in papillary thyroid cancer (PTC), miR-485-5p is sponged by LINC00460 and thereby upregulates Raf1 expression to facilitate PTC progression (46). In addition, in cholangiocarcinoma, miR-485-5p has been demonstrated to negatively regulate FLVCR1-AS1 (47). Furthermore, in non-small cell lung cancer, DGCR5 has been identified to sponge miR-218-5p to promote cancer progression (48).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in papillary thyroid cancer (PTC), miR-485-5p is sponged by LINC00460 and thereby upregulates Raf1 expression to facilitate PTC progression (46). In addition, in cholangiocarcinoma, miR-485-5p has been demonstrated to negatively regulate FLVCR1-AS1 (47). Furthermore, in non-small cell lung cancer, DGCR5 has been identified to sponge miR-218-5p to promote cancer progression (48).…”
Section: Discussionmentioning
confidence: 99%
“…29 FLVCR1-AS1 sponges miR-485-5p to enhance the growth and metastasis of cholangiocarcinoma. 30 LINC01410 has also been shown to sponge several miRNAs, such as miR-532 and miR-3619-5p. 20,22 Therefore, we analyzed the potential miRNAs of LINC01410 in CC.…”
Section: Dovepressmentioning
confidence: 99%
“…The present study demonstrated that lncRNA FLVCR1-AS1 was elevated in CRC tissues compared with adjacent normal tissues, and the upregulated expression of FLVCR1-AS1 was associated with poor prognosis in patients with CRC, thus implying its essential role in CRC progression. Previous studies have shown that the abnormal expression of FLVCR1-AS1 is associated with the tumorigenesis of multiple cancers (24,25). For example, FLVCR1-AS1 was reported to be upregulated in lung cancer and hepatocellular carcinoma, in which it promoted cell metastasis (26) and tumor growth (27), respectively.…”
Section: Discussionmentioning
confidence: 99%